2022
DOI: 10.3390/cells11203286
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Metabolomics Identifies Efflux Transporter Inhibitors in a Routine Caco-2 Cell Permeability Assay—Biological Implications

Abstract: Caco-2 screens are routinely used in laboratories to measure the permeability of compounds and can identify substrates of efflux transporters. In this study, we hypothesized that efflux transporter inhibition of a compound can be predicted by an intracellular metabolic signature in Caco-2 cells in the assay used to test intestinal permeability. Using selective inhibitors and transporter knock-out (KO) cells and a targeted Liquid Chromatography tandem Mass Spectrometry (LC-MS) method, we identified 11 metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…These cells can express morphological and functional characteristics of the small intestine, such as brush borders, tight junctions, intestinal efflux, and uptake transporters, which affect the passage of drugs and food extracts from the intestinal lumen to the bloodstream [ 22 ]. The transport studies using Caco-2 cell monolayers have revealed essential information about intestinal permeability, the transport method (paracellular, transcellular, or active carrier), the function of intestinal metabolism, and the impact of the P-glycoprotein, breast cancer resistance, and multidrug drug-resistance protein efflux system [ 23 ]. The minimum solubility required for an orally active drug is also determined by its intestinal permeability.…”
Section: Resultsmentioning
confidence: 99%
“…These cells can express morphological and functional characteristics of the small intestine, such as brush borders, tight junctions, intestinal efflux, and uptake transporters, which affect the passage of drugs and food extracts from the intestinal lumen to the bloodstream [ 22 ]. The transport studies using Caco-2 cell monolayers have revealed essential information about intestinal permeability, the transport method (paracellular, transcellular, or active carrier), the function of intestinal metabolism, and the impact of the P-glycoprotein, breast cancer resistance, and multidrug drug-resistance protein efflux system [ 23 ]. The minimum solubility required for an orally active drug is also determined by its intestinal permeability.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, in vitro transporter knock-outs may be compensated by upregulation of another transporter. 19 Moreover, for many drug transporters, 107 possible metabolite substrates are not yet known. Despite these limitations, this manuscript is the first attempt to evaluate influx and efflux routes of metabolites in the CNS considering factors influencing metabolite concentrations in the CSF.…”
Section: Discussionmentioning
confidence: 99%